Open and distance education in global environment : opportunities for collaboration - Garg, Suresh; Indira Gandhi National Open University (New Delhi : Viva Books, 2006)
Contributed papers presented at a seminar organized by Indira Gandhi National Open University.
Includes statistical tables.
Includes bibliographical references.
Keywords: Open plan schools -- Congresses; Distance education -- Congresses; Instructional systems -- Designs -- Congresses